Cover Image. (2nd March 2020) - Dong, Huan; Wang, Qiang; Zhang, Guosen; Li, Ning; Yang, Mengsi; An, Yang; Xie, Longxiang; Li, Huimin; Zhang, Lu; Zhu, Wan; Zhao, Shuchun; Zhang, Haiyu; et al.
Abstract : The cover image is based on the Original Research OSdlbcl: An online consensus survival analysis web server based on gene expression profiles of diffuse large B-cell lymphoma by Huan Dong et al., https://doi.org/10.1002/cam4.2829 . Cover image © Huan Dong and Xiangqian Guo Images.